2018
DOI: 10.1177/1369433218788597
|View full text |Cite
|
Sign up to set email alerts
|

A softened membrane model for prestressed concrete composite box girders with corrugated steel webs under pure torsion

Abstract: Torsion can be regarded as a principal factor in some cases, such as in curved girders and eccentrically loaded girders, when conducting the structural analysis of prestressed concrete composite box girders with corrugated steel webs. Recently, a rational model, called the softened membrane model for torsion, was proposed for the torsional analysis of reinforced concrete members; thereafter, this model was extended to prestressed concrete members under pure torsion and called softened membrane model for torsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Due to the integrity of whole cross section, it is inaccurate that the torsional deformation coordination of CBGCSW is only in terms with that of TBSC in previous research (Ko et al, 2013;Mo et al, 2000;Shen et al, 2018aShen et al, , 2018bShen et al, , 2018d. In other words, the twist of CBGCSW is not only related to shear strain and geometry of TBSC, but also related to that of CSW (Nie and Tang, 2007).…”
Section: Torsional Deformation Coordination Of Whole Cross Sectionmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the integrity of whole cross section, it is inaccurate that the torsional deformation coordination of CBGCSW is only in terms with that of TBSC in previous research (Ko et al, 2013;Mo et al, 2000;Shen et al, 2018aShen et al, , 2018bShen et al, , 2018d. In other words, the twist of CBGCSW is not only related to shear strain and geometry of TBSC, but also related to that of CSW (Nie and Tang, 2007).…”
Section: Torsional Deformation Coordination Of Whole Cross Sectionmentioning
confidence: 96%
“…Based on FA theory, Ding et al (2013b) first proposed a theoretical model to calculate the performance of CBGCSW under pure torsion, which was verified by test results in available literature, and Ding et al (2013a) also conducted a test on four scaled specimens to analyze the impact of influencing factors on ultimate torque of CBGCSW, such as thickness of CSW, concrete strength, and type of corrugation shape. Afterwards, considering biaxial constitutive laws of concrete and Poisson effect in post-cracking stage, Shen et al (2018aShen et al ( , 2018b extended softened membrane model (a type of FA theory) for concrete members to single-box multi-cell CBGCSW under torsion, and comparisons of the proposed model with test data showed that the proposed softened membrane model was capable of computing torsional performance of CBGCSW with multi-cell. Besides, Zhou et al (2019) proposed a two-stage shear strain relationship between TBSC and CSW for softened membrane model to calculate the torsional nonlinear performance.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with concrete bridges, steel-concrete composite structure bridges have the advantages of a lower self-weight and a larger span; compared with steel bridges, they have the advantages of less steel consumption, better structural stability, higher bending rigidity, and higher ductility [1][2][3]. However, steel-concrete composite beams are prone to fatigue problems under long-term repeated loading [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%